Pengaruh Fraud Pentagon terhadap Kecurangan Laporan Keuangan dengan Komite Audit sebagai Variabel Moderasi - Afifah Sentani Rahma Nia Luhri; Ayunita Ajengtiyas S Mashuri; Husnah Nur Laela Ermaya (Penerbit Goodwood, 2021)
Purpose: This study aims to determine the effect of the five components from fraud pentagon, namely pressure, opportunity, rationalization, competence, and arrogance moderated by the audit committee on fraudulent financial statements. Research Methodology: This research is a type of quantitative research using secondary data in the form of annual reports and company financial reports. The regression model used in this study is logistic regression which is processed using the STATA version 16. Results: The results of this study are pressure has a significant positive effect on fraudulent financial statements. Meanwhile, opportunities, rationalization, competence, and arrogance do not have an effect on fraudulent financial statements, besides that the audit committee also cannot moderate the effect of the pressure, opportunities, rationalization, competence, and arrogance on fraudulent financial statements. Limitations: The lack of supporting literature obtained by the authors regarding the audit committee that oversees management in the company is used as a moderating variable on the topic of financial statement fraud. Contribution: This study's results can be used as a reference for further researchers and take into consideration for company management, investors, and creditors in making decisions.